Democracy and democratization: Processes and prospects in a changing world - Georg Sorensen (1948- (Westview, 1993)
The book consists of five chapters: 1) introduces different views of democracy, discusses ways of measuring democracy, and identifies the countries that presently qualify as democratic. 2)demonstrates that the process of democratization. 3) concentrates on possible domestic consequences for economic development, welfare, and human rights. 4) turns to the international consequences of democracy. Finally, 5) considers the future of the democracy and democratization against the background of an optimistic and the pessimistic scenario